2017
DOI: 10.1080/13651501.2016.1254802
|View full text |Cite|
|
Sign up to set email alerts
|

Administration of ketamine for unipolar and bipolar depression

Abstract: Ketamine constitutes a novel, rapid and efficacious treatment option for patients suffering from treatment resistant depression and exhibits rapid and significant anti-suicidal effects. New administration routes might serve as alternative to intravenous regimes for potential usage in outpatient settings. However, long-term side effects are not known and short duration of antidepressant response need ways to prolong ketamine's efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 62 publications
1
59
0
1
Order By: Relevance
“…Adverse effects tend to be brief in acute treatment with low doses, but they are more problematic at higher doses or over longer periods of administration [53]. Although acute treatment with ketamine may be neuroprotective, a more prolonged exposure may predispose to neurotoxicity and drug dependence [30]; other long-term adverse effects are not known [45, 47]. …”
Section: What About Ketamine?mentioning
confidence: 99%
See 3 more Smart Citations
“…Adverse effects tend to be brief in acute treatment with low doses, but they are more problematic at higher doses or over longer periods of administration [53]. Although acute treatment with ketamine may be neuroprotective, a more prolonged exposure may predispose to neurotoxicity and drug dependence [30]; other long-term adverse effects are not known [45, 47]. …”
Section: What About Ketamine?mentioning
confidence: 99%
“…A single intravenous dose of ketamine as monotherapy for MDD produces a rapid antidepressant effect that peaks within 24 h, with an overall OR of 7.55 in controlled studies [49]. A review of 12 studies in unipolar depression and 7 in bipolar depression found an overall response rate of 61% at 24 h, with ketamine always being superior to placebo for symptom reduction and for response [47]. However, there has only been one dose-finding study [50], and the optimal dose for an individual patient remains to be determined [8].…”
Section: What About Ketamine?mentioning
confidence: 99%
See 2 more Smart Citations
“…13 Several trials of KIT have reported 25%-79% reductions in severity of depressive symptoms. 6,9,13 Ketamine also rapidly reduced suicidal thoughts in depressed patients within 1 day of treatment, which was partially independent of ketamine's effect on mood. 6,9,13 Ketamine also rapidly reduced suicidal thoughts in depressed patients within 1 day of treatment, which was partially independent of ketamine's effect on mood.…”
Section: Introductionmentioning
confidence: 91%